Characterization of the gene sequence of the peptide transport protein (PepT1) in paiche Arapaima gigas fingerlings - Toledo Valdiviezo, Odalis Epifanía (2019)
The aim of this study was to characterize the PepT1 of pirarucu Arapaima gigas through genomic and proteomic tools. A transcriptomic and proteomic analysis was made from sections of the intestine, spleen, liver and kidney of fingerlings. The transcriptomic analysis allowed obtaining two consensus sequences of 357 and 459 bp. Both fragments showed a high degree of homology (78 and 80%), mainly with nucleotide sequences coding for the PepT1 of Scleropages formosus of the same Order as A. gigas. The proteomic analysis by double mass spectrometry MALDI TOF/TOF allowed to identify 15 peptide sequences of PepT1 in pirarucu. In conclusion, PepT1 was partially characterized in the intestine of pirarucu, which could be used for further studies on the evaluation of its expression.